Determination of stress state and deformations that can appear in tranversal frames of a 48309 dwt bulk carrier - Cosmin Moguș; Anișoara Gabriela Cristea (Annals of "Dunărea de Jos" University of Galaţi: Fascicle XI Shipbuilding, 2023)
The main objective of this study case is to analyze the response in terms of stress and deformation of transversal frames of a bulk carrier that occur due to the applied loads. This assessment helps ensure the safety of the vessel in terms of structural strength and resistance and to determine the best solutions to apply in unfavorable scenarios. The analysis will be performed on a cargo tank, for three static stress cases, the vessel being placed on still water, on sagging and hogging.